A detailed assessment of health status in children with brain tumours in the first year after diagnosis. (29th September 2015) - Penn, A; Lowis, S P; Stevens, MCG; Hunt, LP; Shortman, RI; McCarter, RJ; Curran, AL; Sharples, PM
Abstract : Introduction: Mortality from paediatric brain tumours has fallen significantly over recent years, but few prospective data exist concerning health status (HS). Aims: (1) To compare HS in children with brain tumours after diagnosis with healthy matched controls; (2) To assess the relationship between parent- and self-report HS. Methods: Longitudinal prospective study. Assessments took place approximately 1 (T1), 6 (T6) and 12 (T12) months post-diagnosis. HS was assessed by Health Utilities Index Mark-3 (HUI3) parent-report form at all time-points and child-report form at T12. HUI3 consists of eight attributes (domains), selected according to the importance placed on them by parents in the general public. Results: 29 patients and 32 controls were included in analysis of parent-report, and 21 patients and 22 controls of self-report HS. Median age at T12 was 11.1 years for patients, 10.7 for controls. Patients scored significantly lower than controls for global overall HS assessed by HUI3 Multi-Attribute Function (MAUF) for all comparisons (parent-report, p<0.001 for all time points; self-report p=0.009 at T12). Parent-report HUI3 MAUF improved significantly for brain tumour patients between T1 and T6 (p=0.006), but not between T6 and T12 (p=0.74). Control HUI3 MAUF did not change significantly over time. For parent-report HUI3 MAUF, 21 (81%), 16 (62%) and 18 (62%) patients had scores in the severe/moderate range at T1, T6 and T12 respectively, compared with 6 (21%), 1 (4%) and 4 (13%) for controls. For self-report at T12, 10 (48%) of brain tumour patients and 3 (14%) controls rated their overall HS in the severe/moderate range. Significant differences existed between patients and controls for parent-report single attribute utility functions (SAUFs) at T1 for ambulation, emotion, cognition and pain (maximum p=0.002); at T6 for dexterity, emotion, cognition and pain (maximum p=0.008); and at T12 for cognition (p<0.001). Correlations between parent and self-report HUI3 MAUF, and attributes vision, hearing, speech, ambulation, dexterity and cognition, were good (range rs=0.73–1.0); for emotion, moderate (rs=0.30); and pain, poor (rs=0.20). With the exception of pain, children rated their HS higher than parents. Conclusion: HS is measurable and significantly compromised in children with brain tumours in the first year after diagnosis, but improves with time.